The economic impact of ESG ratings - Florian Berg; Florian Heeb; Julian Kölbel (Leibniz Institute for Financial Research SAFE, 2024)
This study examines the impact of ESG ratings on fund holdings, stock returns, and firm behavior. First, we show that among five major ESG ratings, only MSCI ESG can explain the holdings of US funds with an ESG mandate. We document that downgrades in the MSCI ESG rating substantially reduce firms' ownership by such funds, while upgrades increase it. However, this response in ownership is slow, unfolding gradually over a period of up to two years. This suggests that fund managers use ESG ratings mainly to comply with ESG mandates rather than treating them as updates to firms' fundamentals. Accordingly, we also find a slow and persistent response in stock returns. For a one-year holding period, downgrades lead to an abnormal return of -2.37%. For upgrades, we find a positive but weaker effect. Yet, the extent to which ESG ratings matter for the real economy seems limited. We find no significant effect of up- or downgrades on firms' subsequent capital expenditure. We find that firms adjust their ESG practices following rating changes, but only in the governance dimension
Keywords: G11; G12; G32; G34; 330; Responsible investing; social impact; ESG ratings; asset prices; corporate investment; corporate governance